1993
DOI: 10.1016/0741-5214(93)90064-s
|View full text |Cite
|
Sign up to set email alerts
|

Allograft vein bypass: Is it an acceptable alternative for infrapopliteal revascularization?

Abstract: Unheralded occlusions more typical of prosthetic graft failure tempered the initial enthusiasm and effectiveness of vein allografts. All autogenous options must be exhausted to complete distal, secondary revascularization before resorting to nonautogenous conduits. Use of allograft veins must be viewed with continued skepticism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 29 publications
1
21
1
Order By: Relevance
“…In 1993, Walker et al 9 concluded that CHg offered better results than a synthetic conduit, but its use should be deferred until improved preparation techniques could provide a more durable conduit. Similarly, Harris et al 10 obtained similar unexciting results.…”
Section: Discussionsupporting
confidence: 68%
“…In 1993, Walker et al 9 concluded that CHg offered better results than a synthetic conduit, but its use should be deferred until improved preparation techniques could provide a more durable conduit. Similarly, Harris et al 10 obtained similar unexciting results.…”
Section: Discussionsupporting
confidence: 68%
“…[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Comparison was made difficult because these grafts were used for different indications (some for replacement of infected grafts) and because different methods of harvesting, preservation, and immunosuppressive therapy were used. Through careful graft selection, meticulous immunosuppressive therapy with cyclosporine, and careful follow-up, we could obtain 1-year secondary patency comparable with the best published results.…”
Section: Discussionmentioning
confidence: 99%
“…The infra-popliteal artery to paramalleolar artery bypass has expanded its use because infrapopliteal arterial occlusive disease is the predominant pattern seen in diabetes requiring revascularization and because the prevalence of diabetes and the indications for diabetic interventions arerising dramatically.Like the longer bypasses to the foot, they must be constructed of autogenous vein. Homograft GSV has been advocated but have not been able to achieve durable patency expected with autogenous grafts (17,18). The argument over the superiority of reversed versus nonreversed versus in situ bypass was investigated and most surgeons now agree that all three are equivalent (19).…”
Section: Femoro-popliteal Bypassmentioning
confidence: 98%
“…Like the longer bypasses to the foot, they must be constructed of autogenous vein. Homograft GSV has been advocated but have not been able to achieve durable patency expected with autogenous grafts (17, 18). The argument over the superiority of reversed versus nonreversed versus in situ bypass was investigated and most surgeons now agree that all three are equivalent (19).…”
Section: Infra-inguinal Bypassmentioning
confidence: 99%